(Re)discovering social identity theory: an agenda for multinational enterprise internalization theory. Issue 2 (4th November 2020) - Raskovic, Matevz; Takacs-Haynes, Katalin
Abstract : Purpose: Firm internalization is a central concept within the business strategy literature, as part of the broader social sciences. The purpose of this paper is to show how and where MNE internalization theory can benefit from a social identity theory (SIT) perspective to better understand 21st-century multinational enterprises (MNEs). Design/methodology/approach: This paper provides a review and future research agenda for the use of SIT related to MNE internalization theory. The authors complement an evolutionary review of SIT literature with a systematic bibliometric analysis identifying specific thematic gaps. Extending Buckley and Casson's review of and future research agenda for MNE internalization theory, the authors propose three specific future research directions along with eight guiding research questions. Findings: International business (IB) scholars are familiar with limited aspects of SIT and apply it only in certain research areas, mainly connected to human resource management and leadership, organizational identity and work-related outcomes or international marketing. Strategic management and strategy-oriented IB scholars are less familiar with SIT, despite growing interest in MNE micro-foundations and decision-making under uncertainty. Originality/value: The authors position SIT as a natural meta-theoretical fit to MNE internalization theory. By providing a future research agenda along with eight supporting research questions, the authors help to advance the MNE internalization theory by linking individual, group and intergroup perspectives against a more socially nuanced, interactionist and dynamic view of MNEs and their decision-making.